Apertura radical y conocimiento libre: repositorio de revistas académicas mexicanas de acceso abierto a través de Wikidata - Alvarez-Azcarraga, Luis (Revista Científica, 2023)
This article proposes the possibility of creating an open and free repository of open-access academic journals using Wikidata, Wikipedia, and Zotero. The project starts with only Mexican social sciences and humanities journals. To this effect, some open indices and datasets are taken as a foundation: DOAJ, Latindex, Dialnet, and Latinrev. Even though there are open datasets for academic journals, this work proposes the creation of a database based on radical openness from Wikimedia projects, following the principles of free knowledge and the participation of anyone in the construction of open science. Storing academic journals and papers in Wikipedia also allows performing analyses and cross-referencing information, which may be a complex task in other repositories. This article shows the preliminary results of analysis regarding the publishers, topics, and licenses of Mexican academic journals in the field of social sciences and humanities which have thus far been updated in Wikidata. Another aspect of this study is that it suggests that this open database for academic publications also allows indexing papers and men and women authors, as well as other topics derived from the items added, along with the use of these articles as sources or references for Wikipedia articles.